2015
DOI: 10.1080/15384047.2015.1047569
|View full text |Cite
|
Sign up to set email alerts
|

Novel reversible selective inhibitor of nuclear export shows that CRM1 is a target in colorectal cancer cells

Abstract: Abbreviations: CRM1, chromosomal region maintenance 1; DMSO, dimethyl sulfoxide; EGFR, epidermal growth factor receptor; LMB, leptomycin B; NES, leucine-rich nuclear export signal; PI3K, phosphoinositide 3-kinase; RanBP1, Ran-binding protein 1.Colorectal cancer arises via a multistep carcinogenic process and the deregulation of multiple pathways. Thus, the simultaneous targeting of multiple pathways may be a promising therapeutic approach for colorectal treatment. CRM1 is an attractive cancer drug target, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
(33 reference statements)
0
32
0
1
Order By: Relevance
“…Export of RanBP1 from the nucleus to the cytoplasm depends on the chromosome region maintenance 1 (CRM1)-dependent nuclear export system30, and the down-regulation of RanBP1 resulted in the death of cultured cells3738. Therefore, the finding of marked alteration of the subcellular localization of nucleo-cytoplasmic cargo proteins in this study suggests robust impairment of nuclear function due to cleavage of NPC components such as Nups by calpain in ADAR2-deficient AHCs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Export of RanBP1 from the nucleus to the cytoplasm depends on the chromosome region maintenance 1 (CRM1)-dependent nuclear export system30, and the down-regulation of RanBP1 resulted in the death of cultured cells3738. Therefore, the finding of marked alteration of the subcellular localization of nucleo-cytoplasmic cargo proteins in this study suggests robust impairment of nuclear function due to cleavage of NPC components such as Nups by calpain in ADAR2-deficient AHCs.…”
Section: Discussionmentioning
confidence: 62%
“…Immunoreactivity for cellular apoptosis susceptibility protein (CAS), also known as exportin-2, was predominant in the nucleus of ADAR2-positive motor neurons but was faintly detected in the cytoplasm of ADAR2-deficient motor neurons. Immunoreactivity for RanBP1, which controls assembly/disassembly of certain karyopherin-cargo complexes30, was predominantly cytoplasmic in ADAR2-positive motor neurons but was nuclear or undetectable in ADAR2-deficient motor neurons (Fig. 3b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the sustained proliferation is one of the cancer hallmarks acquired during cancer development and progression (Hanahan and Weinberg, 2011). In this regard, we identified that the overexpression of XPO1 was strongly associated with Ki67 expression, which in turn reflected the implication of XPO1 overexpression in mislocalization of essential cell cycle inhibitory proteins such as p27, p53, cyclins and some apoptotic proteins (Nguyen et al, 2012;Niu et al, 2015) lead to unregulated cell division and increased tumor size. Despite ascending tendency of XPO1 expression was noticed with increased tumor…”
Section: Discussionmentioning
confidence: 63%
“…The number of HT29 cells with Ki67 expression was dramatically and significantly decreased in HT29 KPT-330-treated groups compared to the control, and this confirmed the anti-proliferative effect of KPT-330. In fact, the inhibition of XPO1 activity induced G1 cell cycle arrest with the loss of S, G2, and M phases within hours of application followed by increase of nuclear cell cycle inhibitory proteins such as p27 and p53 (Niu et al, 2015). Normally, the Ki67 is degraded and decreased continuously in G0 and G1, which indicate the decrease of protein synthesis and then accumulate from S to M phases, which indicate an increase of cells proliferative activity.…”
Section: Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation